PREVALENCE, GENETIC VARIABILITY AND POPULATION DIVERSITY OF ALLEXIVIRUSES INFECTING GARLIC IN PAKISTAN - Muhammad Zubair Hamza; Prof. Dr. Muhammad Ashfaq; Dr. Hasan Riaz; Dr Nadeem Ahmed; Dr. Muhammad Ahsan (Journal of Animal and Plant Sciences, 2025)
Garlic (Allium sativum L.) is an important bulbous vegetable, vulnerable to viral infections of different genera particularly Allexivirus genus, known to cause economically significant diseases, leading to havoc yield losses worldwide. This study aimed to assess potential prevalence, genetic variability and population diversity of Allexiviruses in Pakistan. Field surveys were carried out in 2021 and 2022 growing seasons and leaf samples, both symptomatic and asymptomatic were tested using reverse transcriptase polymerase chain reaction (RT-PCR). Total RNA was isolated from leaf tissue and used to synthesize complementary DNA (cDNA) with primers targeting Allexivirus CP and NABP gene and selected samples were further confirmed through PCR amplification. Out of 700, 296 samples were tested positive for Allexiviruses infection and disease prevalence for Garlic virus C (GarV-C) was recorded at 20.85% followed by Garlic virus A (GarV-A) at 11.4% and Garlic virus B (GarV-B) at 7.7% during 2021 season. In 2022 season, GarV-C again showed highest prevalence at 21.14% followed by GarV-B at 14% and GarV-A at 9.4%. PCR amplifications were visualised on a 1% agarose gel, resulting bands of 750 bp and amplified DNA was subsequently purified and cloned for sequencing. Sequence analysis identified two sequences, each comprising of 819 nucleotides corresponding to Garlic virus C (GarV-C) were submitted in Genbank with accession number PP759407 and PP759408. Comparative analysis of nucleotide and amino acid sequence of CP and NABP gene revealed 88%-98% identity between this study isolates and GenBank sequences from Pakistan, China, Japan, Australia, Czech Republic, Poland, and Serbia. Phylogenetic analysis based on nucleotides and amino acid sequences of CP and NABP genes showed that isolates of this study were closely related with GenBank isolates. Analysis of population diversity and selection pressure revealed that GarV-C (CP) gene was under balancing selection associated with contracting population, NABP gene appears to be under negative selection suggesting adaptation in the context of population expansion. This study highlighted the disease prevalence, genetic variability and population diversity of Allexivirus species affecting garlic in Pakistan. These findings will provide valuable insights into the GarV-C population structure and contribute to ongoing efforts focusing virus-free garlic production in Pakistan.
Keywords: Garlic; Allexiviruses; Prevalence; Genetic variability; Population diversity